Euthanasia in the Major World Religions - Angeliki Ziaka (اخلاق وحیانی)
“Euthanasia” or voluntary termination of life is one the most complicated issues in the moral, legal and religious debates nowadays. In the meantime, the role of religions in directing the views of researchers is obvious. In this article, a brief look at the different religions of the world to the issue of euthanasia (whether in the form of active or passive) will be provided as much as possible and we will analyze these ideas. At first, we study three monotheistic religions, Islam, Christianity and Judaism. Hinduism and Jainism, then, will be examined and finally, Far Eastern religions such as Buddhism, Taoism, Confucianism and Shinto school will say about euthanasia.